Sheikh Jamil Al-Husaini’s Analysis Method For Gharib Hadiths; Critical Study of the Book al-Qamar al-Sari li Idah Garib Sahih al-Bukhari - Shofiatun Nikmah Nikmah (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2021)
Sheikh Jamil Halim al-Husaini has contributed greatly to the study of hadith in the global era. His students are scattered in the word, including the archipelagi. However, Research on his character in the field of hadith has not been done. This Research will examine of Sheikh Jamil al-Husaini in the field of hadith by conducting a critical study of his work entitled al-Qamar al-Sa>ri> li I>dah Gari>b Sahi>h al-Bukha>ri. >This book will be studied critically to find out how Sheikh Jamil al-Husaini’s concept is in understanding the Gharib Hadiths. This research uses a qualitative method with a historically approach, this approach will describe comprehensively the intellectual journey and the background of the book in the field of hadith. This research can show that Sheikh Jamil al-Husaini uses the mujadalah method to explain the gharib hadiths in his book. He denied the understanding that was considered incorrect in understanding the Gharib words in the Hadith, especially understanding that is contrary to sunni understanding. Conceptually, Sheikh Jamil al-Husaini understands Gharib hadith based on three concepts, namely, 1) interpreting the argument of the Koran and Hadiths that are relevant to the word gharib. 2) conducting linguistic analysis 3) expressing the opinion of the salaf scholars from sunni and refuting arguments that contradict the meaning of hadith. Sheikh Jamil al-Husaini also gave his personal arguments in every explanation in his book. This book shows that Sheikh Jamil al-Husaini had expertise in the field of hadith. His Contribution to the study of Hadith has also reached the archipelago. Sheikh Jamil al-Husaini also transmitted hadith with his complete sanad to his students in the archipelago, either via virtual or in person.",